Data Privacy and Cyber Security in the Age of IoT and Data Analytics: Response of Law - Salpekar, Rashmi (International Journal of Engineering and Technology, 2018)
IoT and Data Analytics are developing and adopted very fast. Utilities are deploying smart meters, smart lighting, etc. Even the water supply distribution agencies are deploying smart water schemes to reduce non-revenue water. Further, data analytics is done by loT of companies to provide targeted advertising and knowing user preferences. All this requires collecting user data to be effective.There is an urgent need to define unambiguous laws, well defined dispute resolution that defines the consumer liability and service provider liability in light of court judgments to that effect. Further, a cyber security framework also needs to be defined and also a cyber security maturity model needs to be in place to rate the cyber security of a given agency and the steps needed to make cyber security better.The paper intends to study national and international laws on cyber security including framework and maturity model and data privacy laws. It will then come up with concrete enforceable suggestions to make cyber security better. The suggestions will include laws, liability, framework and guidelines.Â Â